Acute Respiratory Distress Syndrome and Hepatotoxicity Associated with Single Dose Nitrofurantoin Use. (27th November 2012) - Sargın, Gokhan; Elbek, Osman; Balantekin, Cem; Meteoglu, İbrahim and Culhacı, Nil
Abstract : Nitrofurantoin is a synthetic nitrofuran compound. It is generally used in urinary tract infections, either alone or in combination with other antibiotics. A number of adverse effects may develop in different body systems during nitrofurantoin treatment; however, concomitant pulmonary and hepatotoxicity are rare. In this paper, we present a case of acute respiratory distress syndrome and hepatotoxicity following administration of a single dose of nitrofurantoin.